Chapter A test facility to investigate sheath effects during ion cyclotron resonance heating - Crombé, Kristel (InTechOpen, 2019)
Nuclear fusion is a promising candidate to supply energy for future generations. At the high temperatures needed for the nuclei to fuse, ions and electrons are no longer bound into atoms. Magnetic fields confine the resulting plasma. One of the heating methods is the ion cyclotron resonant absorption of waves emitted by an external Ion Cyclotron Radio Frequency (ICRF) antenna. The efficiency of ICRF heating is strongly affected by rectified RF electric fields at antenna and other in-vessel components (so-called 'sheath effects'). The chapter presents an overview of ICRF principles. Attention is given to characterising the detrimental sheath effects through experiments on a dedicated test facility (IShTAR: Ion cyclotron Sheath Test ARrangement). IShTAR has a linear magnetic configuration and is equipped with an independent helicon plasma source. The configuration and capabilities of the test-bed and its diagnostics are described, as well as an analysis of the plasmas.